Unraveling the Mechanisms of the Apis mellifera Honeycomb Construction by 4D X‐ray Microscopy. Issue 42 (12th September 2022) - Franklin, Rahul; Niverty, Sridhar; Harpur, Brock A.; Chawla, Nikhilesh
Abstract: Honeycomb is one of nature's best engineered structures. Even though it has inspired several modern engineering structures, an understanding of the process by which the hexagonal cells are formed in 3D space is lacking. Previous studies on the structure of the honeycomb are based on either 2D microscopy or by direct visual observations. As a result, several critical features of its microstructure and the precise mechanisms of its growth are not well understood. Using 4D X‐ray microscopy, this study shows how individual and groups of honeycomb cells are formed. Cells grow additively from a corrugated central spine in a dynamic manner. The previously undocumented, corrugated spine contributes significantly to the comb's robust mechanical properties in all three dimensions. As cells grow, honey bees create a "coping, " which this study shows to be the location where new wax material is deposited behind where compaction and densification take place. This is exemplified by pores in the wax observed at the coping and alternating rear junctions between the comb cells that arise from the additive building technique and the highly efficient cell packing methodology, respectively. Additional mechanisms for growth and formation are discussed and described. Abstract : Using X‐ray microscopy, a millennium‐old question of how bees build combs is answered. Individual cells are seen to grow out of the spine, which behaves as a substrate from which the hexagonal geometry is directly adopted. Seminal features such as the corrugated spine, coping, and porosities are observed, that further give us significant insights into the comb's construction and properties.